2015
DOI: 10.19030/jdm.v5i2.9569
|View full text |Cite
|
Sign up to set email alerts
|

Impact Of Job Analysis On Job Performance: Analysis Of A Hypothesized Model

Abstract: The manuscript entitled Impact of Job Analysis on Job Performance: Analysis of a Hypothesized Model was retracted on December 17, 2015. Please contact our office at Journals@CluteInstitute.com for more information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Also, it could effectively increase the collaboration and responsiveness, and increase productive and competitive advantage within its industry (Mahapa, 2013). However, it should be noted that when it comes to the knowledge, skills, and abilities (KSA) or the competency level of an employee regarding them offering quality performance in their given task or job (Safdar, Waheed & Rafiq, 2010). Then, the KM theory could be used in seeking skilled recruits by using job analysis techniques.…”
Section: Hr Management Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it could effectively increase the collaboration and responsiveness, and increase productive and competitive advantage within its industry (Mahapa, 2013). However, it should be noted that when it comes to the knowledge, skills, and abilities (KSA) or the competency level of an employee regarding them offering quality performance in their given task or job (Safdar, Waheed & Rafiq, 2010). Then, the KM theory could be used in seeking skilled recruits by using job analysis techniques.…”
Section: Hr Management Practicesmentioning
confidence: 99%
“…This process was able accurately to identify each occupation regarding its duties, instrument required, must methodology for the operation and the sequencing of the working conditions. However, it should be noted that HR researchers have found that cultural regions, such as Pakistan which is a border neighbor of India that job analysis practice has not yet thoroughly been tested but acknowledged as an acceptable practice to evaluate employee job performance (Safdar, Waheed, & Rafiq, 2010).…”
Section: Hr Job Analysis Processesmentioning
confidence: 99%